Preparation of Module 1 of the Registration Dossier According to the EAEU Procedure - E. M. Rychikhina (Регуляторные исследования и экспертиза лекарственных средств)
The legislation of the Eurasian Economic Union (EAEU) includes all the necessary requirements and tools to implement a unified approach to preparing Module 1 of the electronic Common Technical Document (eCTD) for the concerned member states (CMSs). However, the approaches to the matter and the recommendations provided to applicants differ across member states. This causes significant ambiguity and imposes an excessive burden on the applicants. Drafting of a guideline on preparation of eCTD Module 1 for the CMSs will allow for tackling this important grey area in the EAEU regulatory framework, as regulatory authorities are lacking consensus on country-specific submissions. Currently, pharmaceutical industry stakeholders consider the Russian experience of implementing the legislation in question the most successful, so it is proposed to convey this experience to the common market of the EAEU.